Dendritic core-shell nickel-iron-copper metal/metal oxide electrode for efficient electrocatalytic water oxidation - Peili Zhang (Nature Portfolio, 2018)
Splitting water into high-energy fuel represents a renewable way to generate energy, yet the sluggish oxidation kinetics drives up technological costs. Here, the authors prepare tri-metallic core-shell electrodes using nickel, iron, and copper metals to accelerate electricity-driven water splitting.